THE STRATEGY OF DEVELOPMENT JAKARTA WALKING TOUR - Musthofa, Budiman Mahmud; Arif, Muhamamd (Journal of Indonesian Tourism and Policy Studies, 2020)
The central government has designated DKI Jakarta as one of the priority areas for Indonesia's tourism development. One of the tours that is currently being developed is the Jakarta Walking Tour. Therefore, the study of the Jakarta Walking Tour tourism development strategy is interesting to do. Data collection methods used in this study were interviews, observation, and literature study. The results show that the Jakarta Walking Tour development strategy is on the track and has shown the synergy of various Jakarta tourism stakeholders. Currently there are 6 Jakarta Walking Tour routes, but these routes must be continuously developed so that more alternative travel trips can be made. In terms of promotion, it must be further enhanced by using various media so that it is better known by the wider community.